2023
DOI: 10.1002/jper.23-0079
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of systemic inflammation in the association between heavy metals exposure and periodontitis risk

Mi Du,
Ke Deng,
Qingqing Cai
et al.

Abstract: BackgroundThis study evaluated the mediating role of systemic inflammation in the association between exposure to heavy metals and periodontitis in a nationwide sample of adults.MethodsPooled cross‐sectional data from the National Health and Nutrition Examination Survey (NHANES 2009‐2014) were used (n = 8993). Periodontitis was defined by a full‐mouth examination and classified as no/mild and moderate/severe (mod/sev) groups. Blood and urinary heavy metal levels were investigated, including cadmium (Cd), lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Although NHANES analytical protocol recommended combine different cycles to recruit more participants and improve the stability of data estimates, we only select NHANES 2013–2014 because only this cycle documented full information on both HbEO and periodontitis ( 53 ). Although the association between ethylene oxide exposure and periodontitis could be affected by other environmental pollutant exposure, such as heavy metals and multiple polyaromatic hydrocarbons ( 54 , 55 ), we could not consider these above due to limited participant number. And we did not classify the severity of periodontitis in our statistical analysis due to limited number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Although NHANES analytical protocol recommended combine different cycles to recruit more participants and improve the stability of data estimates, we only select NHANES 2013–2014 because only this cycle documented full information on both HbEO and periodontitis ( 53 ). Although the association between ethylene oxide exposure and periodontitis could be affected by other environmental pollutant exposure, such as heavy metals and multiple polyaromatic hydrocarbons ( 54 , 55 ), we could not consider these above due to limited participant number. And we did not classify the severity of periodontitis in our statistical analysis due to limited number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Prior evidence based on population studies has demonstrated a correlation between cadmium metabolite levels and periodontitis. 12,[44][45][46] Furthermore, an animal study conducted experimentally has identified a significant influence of cadmium on periodontal bone, thereby suggesting its potential contribution to periodontal disease in humans. 15 Given that periodontitis is a disease with a cumulative effect on alveolar bone loss, we cannot rule out the hypothesis of a possible existing accidental association based on the cumulative effects of both factors, which needs to be further explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in this study, three main models (multiple logistic regression, BKMR and WQS) were used to explore the association between blood metals and periodontitis, which make the results more comprehensive. Second, while a recent study touched on a similar topic, 46 it primarily focused on the individual analysis of three metals. In contrast, our research incorporated a broader range of metals (10 types) and employed two statistical methods to assess the combined effects of these metallic elements, emphasizing the role of metal mixtures.…”
Section: Discussionmentioning
confidence: 99%